Stock Market Reactions to Operational Loss Announcements in Financial Institutions in Emerging Markets and Developing Economies - Tubeileh, Dana (2016)
In this paper, we analysed stock market reactions to operational loss announcements in emerging markets and developing economies. More precisely, we are interested in determining what firm specific characteristics, macro-economic variables, and other factors have an impact on the stock market reactions of firms suffering operational losses. This study is based on a sample of 160 operational loss events stemming from ORIC database. All loss events affected financial institutions in emerging and developing countries in 2014 and 2015. Results showed that all types of operational losses (pure losses, legal lawsuits’ losses, and regulatory announcements’ losses) do not produce negative and significant stock price reactions. Multivariate regression results suggested that adverse stock market reactions are influenced by operational losses occurring in the private banking business line. In addition, we provided evidence that top executives’ involvement in operational losses leads to more adverse stock market reactions. Finally, we found that the reputational loss resulting from the operational loss announcement, the event type of the loss, firm’s size, firm’s aggressive growth in liabilities, and firm’s recognition of the loss have no impact on the stock market reactions of the firm bearing the loss.